Prosthetic valve endocarditis presenting with back pain alone: A case report - Sato, Toshihiro (J Gen Fam Med, 2020)
We report a case of a 64‐year‐old woman with a past medical history (PMH) of prosthetic valve replacement 7 months prior to admission, who presented with only right back pain. Physical examination revealed one conjunctival spot hemorrhage and a mild systolic murmur. Blood cultures were positive for methicillin‐resistant Staphylococcus epidermidis. Trans‐esophageal echocardiography revealed aortic valve vegetations; hence, a diagnosis of prosthetic valve endocarditis (PVE) was made. Clinical presentation of infective endocarditis varies and sometimes mimics that of polymyalgia rheumatica. The patient was diagnosed as PVE considering the whole clinical picture including the patient's PMH, physical examination, and blood cultures.